Eficiência do azul de metileno na avaliação da qualidade hídrica da Sanga da Brandina em Caçapava do Sul - RS - (:unkn) unknown (Universidade Federal do Pampa, 2018)
One of the biggest environmental challenges is to keep the reserves of our planet’s water quality. This fact if must mainly the use of water to urban sprawl and a varied set of economic activities. In this perspective, they become necessary appropriate knowledge of the self-depuration potential of the water resources and the proper preservation of water springs, establishing an austere control regarding the quantity and quality of water, ensuring the supply of mankind and other living beings for their basic needs. The water pollution caused by human actions, through the introduction of inorganic or organic substances, ends up generating harmful effects such as: human health risk: damage to living things; and prejudice to the quality of water for use in your comercial activities. The preservation of the environment and especially the quality of the water available is essential for the continuation of life on our planet. Sometimes, the use of products to identify possible contamination has high cost. However, the use methylene blue (MB) which presents the function of reductant agent interacting with organic matter, if shows simple and effective at a more affordable price. The present work uses simple methods and of low cost, for verification of the quality of the water, through the oxidation of the indicator. The results obtained in the analyses confirm that the used color presents reaction with the present organic matter in the course of water that is being studied, tends in some of the collections almost 100% of reduction of the coloration and of the concentration of blue of metileno of the brackets, this way that supposes that there is contamination in the quality of the water of Sanga of Brandina. With the aid of the quality parameters the acquired data in the accomplished methods could be justified, demonstrating the method of the Blue of Metileno as soon as should be considered as secondary indicator.
Keywords: Contaminação da água; Indicador secundário; Matéria orgânica; Contamination of the water; Secondary indicator; Organic matter; CNPQ::CIENCIAS EXATAS E DA TERRA